2004
DOI: 10.2337/diacare.27.5.1071
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Gastroparesis by High-Frequency Gastric Electrical Stimulation

Abstract: OBJECTIVE -To investigate the long-term efficacy of high-frequency gastric electrical stimulation (GES) for treating diabetic gastroparesis. RESEARCH DESIGN AND METHODS-This is a retrospective review of 48 adult diabetic patients with refractory gastroparesis who had a GES system implanted surgically and had follow-up evaluations at 6 and 12 months. The outcome measures were total symptom score (TSS), derived from six upper gastrointestinal (GI) symptom subscores; health-related quality of life (HQOL), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 28 publications
5
153
0
2
Order By: Relevance
“…There have been other studies reporting on an individual institution's experience with Enterra GES [4][5][6][10][11][12]. In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…There have been other studies reporting on an individual institution's experience with Enterra GES [4][5][6][10][11][12]. In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Near-completion gastrectomy (NCG) has proved useful in small series of patients [21] , but data on longterm follow-up has been lacking. Gastric electrical stimulation can be of value in the management of gastroparesis [22][23][24] , in which the patients with PGS received continuous highfrequency/low-energy gastric electrical stimulation via electrodes deposited in the muscular wall of the antrum and connected to a neurostimulator in an abdominal wall pocket. This method produced entrainment of the intrinsic slow wave and promoted contractions in phase III with the normal slow wave.…”
Section: Discussionmentioning
confidence: 99%
“…The key questions needing answer are which patients are likely to respond, the optimal electrode placement, and the optimal stimulation parameters, none of which had been rigorously evaluated (American Gastroenterological Association Technical Review on the Diagnosis and Treatment of Gastroparesis) [35] and still have not been so far. This is the reason why other experiments have been performed during the last few years, including the one by Lin's group [36] who retrospectively reviewed all patients undergoing GES implantation at the University of Kansas Medical Center (KUMC) from 1998 to 2002, to analyze the effects of GES on symptoms, health-related quality of life (HQOL), nutritional status, GE, and the degree of glucose control in 48 diabetic patients who had medically refractory gastroparesis and at least 12 months of follow-up available.…”
Section: Medical Treatment and Gastric Electric Stimulationmentioning
confidence: 99%